TRANSLATION INCONSISTENCIES OF EDUCATIONAL TERMS - Laizāne, Inga; Miķelsone, Ilze; Koķe, Tatjana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The article by means of extended literature review draws attention to the most common translation inconsistencies that arise in the rendering of word combinations with the concepts education and learning from English into Latvian and vice versa. The novelty and topicality of the article is related to the need to highlight the transformation of the understanding of concepts in connection with the modernization and changes in the field of education. The study was implemented as an interdisciplinary research analysing Latvia’s education policy documents, dissertations, monographs, encyclopaedias, dictionaries and glossaries using induction, deduction and comparison methods. The research findings allow to emphasize the following major translation inconsistencies: superficiality in distinguishing the substantive meaning of the concepts “education” and “learning”, incorporation of the substantive meaning of two terms into one term, direct adoption of Anglicisms into Latvian, lack of equivalents in Latvian language, use of several similar concepts to render one English term into Latvian that embarrasses the perception of the terms’ meaning.